Experimental study of cyclic fatigue of nickel-titanium rotating endodontic instruments with controlled shape memory T C-Files Gold STEA (V ideya) - V. V. Tairov; А. А. Adamchik; E. Yu. Mendosa; L. А. Mamedova; M. D. Filippova; V. V. Dorogan; M. V. Savina (Эндодонтия Today)
INTRODUCTION. The dental market is constantly being replenished with new endodontic rotary instruments. Particular interest is drawn to the safety of using rotary files made in China from new nickel-titanium alloys with controlled memory wire (CM-Wire), which have undergone special treatment to enhance their elasticity and breakage resistance.AIM. Experimental evaluation of the cyclic fatigue resistance of new endodontic rotary instruments TC-Files Gold STEA (manufactured by VIDEYA, China), made from CM-Wire alloy, using models that simulate root canals of varying anatomical complexity depending on the angle of curvature and radius of root curvature.MATERIALS AND METHODS. Original models (patent application No. 2026183756) were used for testing, simulating three types of root canal curvatures: 45°, 90°, and an S-shaped curvature (450 and 600) with root curvature radii of 5 mm and 7 mm, respectively, and 5 mm and 3 mm for the S-shaped curvature. Nickeltitanium TC-files Gold STEA instruments of sizes 20/02, 15/03, 20/04, 25/04, 25/06, 30/04, 30/06, and 35/04 were sequentially fixed in the Geosoft Endoest endomotor. A total of 240 files were tested in the experiment, with 30 instruments of each size tested until breakage. The following parameters were set on the endomotor for all instruments: rotation speed of 250 RPM and torque of 3 N·cm. The files were inserted into a groove of the corresponding size, the endomotor was turned on, and the time until the instrument broke was recorded. The average time to breakage was calculated for each instrument size. Using a caliper, the length of the broken piece of each instrument was measured, and the average breakage length for each instrument size was determined. The number of cycles to breakage was also calculated. Statistical analysis of the obtained results was performed using multifactorial ANOVA in Statistica 13 software.RESULTS. The highest resistance to cyclic loads in the root canal models with a 45° curvature and a 5 mm radius of curvature was demonstrated by TC-files Gold STEA size 20/04. In the root canal models with a 90° curvature and a 7 mm radius of curvature, as well as with an S-shaped curvature at angles of 45° and 60° and radii of curvature of 5 mm and 3 mm, respectively, the TC-files Gold STEA size 15/03 showed the greatest resistance. The lowest resistance to cyclic loads in the root canal models with a 45° curvature and a 5 mm radius of curvature was observed in TC-files Gold STEA size 35/04. In the models with a 90° curvature and a 7 mm radius of curvature, the least resistance was found in TC-files Gold STEA size 30/06, while in the models with an S-shaped curvature at angles of 45° and 60° and radii of curvature of 5 mm and 3 mm, respectively, the least resistance was shown by TC-files Gold STEA size 30/04. For all instrument sizes, breakage occurred most quickly when rotating in S-shaped canals. For six of the eight sizes (TC-files Gold STEA sizes 20/02, 15/03, 25/04, 25/06, 30/04, and 35/04) produced by Videya, cyclic fatigue accumulated faster when the instruments were rotated in root canal models with a 45° curvature and a 5 mm radius of curvature, compared to the models with a 90° curvature and a 7 mm radius of curvature.CONCLUSIONS. The resistance of files made from CM-Wire alloys to cyclic fatigue depends on the size, taper, design of the instrument, and the anatomical complexity of the root canal. The risk of instrument breakage is highest in S-shaped root canal curvatures. In S-shaped canals (curvature of 45° with a radius of 5 mm and curvature of 60° with a radius of 3 mm), TC-files Gold STEA instruments with .04 and .06 tapers are not recommended. A root curvature of 45° with a 5 mm radius may be more dangerous for most sizes of CM-Wire alloy instruments than a 90° canal curvature with a 7 mm radius. Therefore, when diagnosing the complexity of root canal anatomy, both the angle of the root canal curvature and the radius of the curvature should be taken into account.